Journey to the South: Consequences of inadequate Family care and National response to Kayayei in Ghana - Sylvester Kyei-Gyamfi; Theophilus Kwabena Abutima; Bernard Akyeampong Amoh (Social Work and Society, 2024)
The difficulties of girls working in the "Kaya" trade in Ghana's urban markets are the main subject of this policy review paper. It is to demonstrate the ineffectiveness of the family and the government in dealing with "Kayayie" in Ghana. The paper largely adopted a desk study approach, the main sources being scholarly studies, and a review of information from government agencies, with the addition of the authors' observations and experiences with Kayayie. The argument of the paper is based on Everett Lee's (1960) Push and Pull Model, which describes migration in terms of factors making people move out of their origins. The paper concludes that budget issues hinder the government's ability to address the kayayei phenomenon. The paper suggests that the government prioritize the welfare of "Kayayei" in the national budget and consider a nationwide data-collection exercise to generate accurate data on kayayei for improving programming and policy decisions regarding kayayei. The results also show that some families push their daughters into marriage to profit from it, while some girls are compelled to travel to the South to avoid being forced into marriage. Since families are primarily responsible for meeting their children's needs, there is a need to improve family life education about the importance of being more accountable for the maintenance of children in the sending communities as well as other migration-prone communities.